Survey of the reproductive development of field-caught Halyomorpha halys (Hemiptera: Pentatomidae) in the Niagara Region of Ontario, Canada. Issue 3 (18th March 2019) - Frewin, Andrew J.; Scaife, Kevin; Fraser, Hannah; Scott-Dupree, Cynthia D.
Abstract: Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), also known as the brown marmorated stink bug, is an invasive agricultural and nuisance pest. Knowledge of the life history of insect pests is important for informing pest management activities. Some North American populations of H . halys have two generations per year, and it is suspected that H . halys may have a partial second generation in the Niagara Region of Ontario, Canada. We determined the number of H . halys generations in Ontario by examining the reproductive development of field-caught adult females. The pattern of reproductive development we observed supports the conclusion that H . halys complete one generation per year in the Niagara Region of Ontario. Reproductively active H . halys were captured as early as May and continued until early September, and the peak of reproductively active individuals occurred between 250 and 550 degree days calculated with a sine-wave function and a lower threshold set to 14.17 °C.